2023
DOI: 10.3390/diagnostics13020276
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography in Bruxism—Not Yet Ready for Clinical Routine

Abstract: Ultrasound shear wave elastography (SWE) is an emerging modality for the estimation of stiffness, but it has not been studied in relation to common disorders with altered stiffness, such as bruxism, which affects almost one-third of adults. Because this condition could lead to an increased stiffness of masticatory muscles, we investigated SWE in bruxism according to a proof-of-principle and feasibility study with 10 patients with known bruxism and an age- and gender-matched control group. SWE of the left and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Jafari et al [15] reported greater MM thickness in bruxers. However, Tetsuka et al [16] and Toker et al [17] measured thinner, narrower, and shorter MMs in the relaxed jaw.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Jafari et al [15] reported greater MM thickness in bruxers. However, Tetsuka et al [16] and Toker et al [17] measured thinner, narrower, and shorter MMs in the relaxed jaw.…”
Section: Discussionmentioning
confidence: 93%
“…Quantifying the size of MM has limited value because of the difficulty of defining normalized dimensions due to the many variables that affect muscle size, such as age, gender, body mass index, and certain medical problems. However, studies have shown that there is a noticeable difference in muscle size, especially during relaxation, in bruxism patients compared to normal individuals, although a cut-off value could not be determined [15,17]. Jafari et al [15] reported greater MM thickness in bruxers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research endeavours in the realm of jaw pain among divers are underway. With the advent of new tools such as advanced three-dimensional (3D) US or US shear wave elastography (SWE) [ 44 ], conducting projects in this field will become more feasible and may uncover new insights. Another intriguing prospect is the utilization of artificial intelligence (AI), which is still in its nascent stages.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic SWE is a new imaging method that has been applied to the quantitative assessment of tissue elasticity [ 20 , 31 33 ]. SWE technology has been used to assess the elasticity of the upper trapezius muscle and its influencing factors [ 21 ], in joint laxity [ 20 ], identifying plantar fasciitis [ 22 ], in the screening of polymyositis (PM) and dermatomyositis (DM) [ 23 ], and assessment of the difference between benign and malignant thickening of the gallbladder wall [ 24 ].…”
Section: Discussionmentioning
confidence: 99%